Sri Lanka: Human Rights in the Context of Civil War - Cheran, Rudhramoorthy (Refuge: Canada’s Journal on Refugees, 1999)
Violations of human rights in Sri Lanka have been fairly well documented. Unfortunately, the conflict in Sri Lanka, despite its intensity, has not attracted appropriate international attention. This article is a review of the current human rights situation in Sri Lanka in the context of civil war. The article also evaluates the prospects for peace building amidst heightening ethnic tensions, emergency regulations, and the lack of democratic governance in the southern part a region which is outside the conflict zone.